Análisis de la cartera de crédito de la Cooperativa de Ahorro y Crédito Educadores de Loja Periodo 2014 - 2015 - Riofrío Mendoza, Diego Santiago (2017)
The research work was carried out in the financial institution that offers its services to the teachers of the magisterium of the province of Loja, for which it was formulated the objective of "Analyzing the credit portfolio of the Cooperative of Savings and Credit Educators of Loja period 2014 - 2015 ", for which specific objectives were developed: Analyze the dispositions established by the regulators of the cooperatives and how these intervene in the policies of the Cooperative under study; Examine how the credit portfolio of the Cooperative is structured; Assess the level of credit risk during the period 2014-2015; To carry out a study of the payment capacity of the partners and their adaptation to the new regulations. In order to carry it out, the general view of the situation of the cooperative was examined through the examination of the institution's historical behavior, through the exploration of provisions that regulate cooperatives and how they influence within the institution mainly in the credit portfolio fulfilling the first proposed objective. Concluding that the main cause is described as the suspension of the monthly contributions through the discount of the role of payments at the beginning of 2015 by the Education Districts, generating delays in payments and uncertainty within the partners; causing the partners to enter into arrears. Subsequently, a comparison of the structure and composition of the credit portfolio of the years of study was made using the vertical analysis to determine how each account of the total portfolio is represented in its respective period; and horizontal to establish the variations occurred between both years. In order to assess the level of risk, it was carried out through the application of financial indicators to determine the level of delinquency of the credit portfolio and its variation from 0.44% in 2014 to a high level of 49.53% at the end of 2015, given that the credit portfolio is mostly 55% consumer credit. For the study of the payment capacity of the partners, the credit applications were analyzed, and the use of computer tools as credit simulators, which allowed to 5 determine that 73.55% is in optimal conditions to fulfill the obligations acquired and the 26.45% has an average deficit of -7.14% for compliance with the monthly payment of the requested credits. The cooperative was faced with scenarios not contemplated as external risks that directly affected the operational stability of the institution causing a rise in delinquency rates, the immediate action taken by the authorities of the same influenced to a large extent in the Mitigation of this impact.